Reduced dose to small bowel with the prone position and a belly board versus the supine position in neoadjuvant 3D conformal radiotherapy for rectal adenocarcinoma. Issue 2 (28th July 2016) - White, Rohen; Foroudi, Farshad; Sia, Joseph; Marr, Mary Ann; Lim Joon, Daryl
Abstract: Introduction: No consensus exists regarding the optimal treatment setup for neoadjuvant radiotherapy of rectal cancer using a 3D conformal (3D CRT) technique. Positioning the patient prone with a belly board aims to reduce the amount of small bowel irradiated. Methods: Twenty‐five patients with locally advanced rectal cancer underwent computed tomography (CT) planning for neoadjuvant chemoradiotherapy. Patients were simulated prone with a belly board and then in the supine position. Questionnaires rating the comfort of each position were completed. 3D CRT plans were generated for both positions to a prescribed dose of 50.4 Gy in 1.8 Gy daily fractions. Dose–volume parameters in 5 Gy increments for small bowel, large bowel and bladder wall were compared. Results: Small bowel V5 Gy, V10 Gy, V15 Gy and V20 Gy values were significantly higher in the supine position (398, 366, 245, 151 cm 3 for supine vs. 243, 213, 161, 122 cm 3 for prone respectively; P < 0.001, <0.001, <0.001 and 0.025). Large bowel V5 Gy, V10 Gy and V15 Gy values were significantly higher in the supine position (266, 209, 147 cm 3 supine, 175, 139, 108 cm 3 prone respectively; P = 0.001, <0.001, 0.003). There was a significant difference in comfort scores favouring the supine position ( P = 0.015). Conclusion: A significant increase in small and large bowel dose was seen in the supine plans. Treatment in the prone position with a belly board may reduce toxicity when using a 3D CRT technique. Whilst both setup positions were tolerable the supine was more comfortable. Abstract : This radiotherapy planning study demonstrates statistically significant dose reductions to small bowel with the prone position and a belly board versus the supine position when using 3D conformal radiotherapy for neoadjuvant rectal cancer. It further suggests that both positions are tolerable although the supine position scored significantly better for comfort.